Characterization of Thorium-bearing Minerals Using Micro-XRF in Metamorphic Rocks of Harau, West Sumatera - Tyto Baskara Adimedha; Heri Syaeful; Frederikus Dian Indrastomo; Ngadenin Ngadenin; Windi Anarta Draniswari (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2022)
In 1974, BATAN conducted a survey to review the potential of radioactive minerals in Harau, West Sumatra. The survey shows that there are radiometric anomalies in several locations in the area. However, the survey has not been able to show the radioactive elements and minerals found in Harau. This study aims to identify and characterize radioactive elements and minerals in Harau. To prove that detailed geological mapping, radiometric mapping with Gamma Spectrometer RS-125, and analysis using Micro-XRF "M4 Tornado Plus®". The results of geological and radiometric mapping show that there are high thorium contents in the metamorphic rocks of the Kuantan Formation reaching 2300 ppm eTh. Identification of thorium-bearing minerals using a micro-XRF instrument resulted in thorium-bearing minerals found in the Harau area are thorite (ThSiO4), yttrialite (YThSi2O7), and monazite ((Ce,Nd,Th)PO4) with thorium levels within 2.75 - 42.75% ThO2 but experiencing a significant increase in Fe. In principle, micro-XRF analysis can identify minerals well, but this analysis can be supported by other analyzes so that it can provide much more precise results. This research is expected to provide information about the occurrences of thorium-bearing minerals in Harau, West Sumatera.